Sociological Perspectives on Urban Gentrification and Its Societal Implications - Alia, Siti; Maulana, Rio Yusri (Journal of Current Social and Political Issues, 2023)
This paper provides a sociological perspective on urban gentrification and its societal implications, employing a research method that primarily involves an extensive literature study. Gentrification, characterized by the influx of more affluent residents into previously disadvantaged urban neighborhoods, is a multifaceted phenomenon with significant social, economic, and cultural consequences. Drawing on sociological theories and empirical research from existing literature, the study examines the drivers and consequences of gentrification, exploring issues such as housing affordability, displacement, social demographics, and the dynamics of urban change. It also considers how gentrification both perpetuates and alleviates social inequalities, emphasizing the importance of inclusive urban development policies and community-based initiatives to address the challenges and opportunities that gentrification presents in contemporary cities.